Examining the Interactions Between Expectations and tDCS Effects on Motor and Cognitive Performance - Rabipour, Sheida; Vidjen, Petar Sefik; Remaud, Anthony; Davidson, Patrick S. R.; Tremblay, François (Frontiers in Neuroscience, 2019)
Background: Despite a growing literature and commercial market, the effectiveness of transcranial direct current stimulation (tDCS) remains questionable. Notably, studies rarely examine factors such as expectations of outcomes, which may influence tDCS response through placebo-like effects. Here we sought to determine whether expectations could influence the behavioral outcomes of a tDCS intervention. Methods: Through an initial study and self-replication, we recruited 121 naïve young adults 18–34 years of age (M = 21.14, SD = 3.58; 88 women). We evaluated expectations of tDCS and of motor and cognitive performance at three times: (i) at baseline; (ii) after being primed to have High or Low expectations of outcomes; and (iii) after a single session of sham-controlled anodal tDCS over the left or right motor cortex. Before and after stimulation, participants performed the Grooved Pegboard Test and a choice reaction time task as measures of motor dexterity, response time, and response inhibition. Results: Repeated measures ANOVA revealed that participants had varying, largely uncertain, expectations regarding tDCS effectiveness at baseline. Expectation ratings significantly increased or decreased in response to High or Low priming, respectively, and decreased following the intervention. Response times and accuracy on motor and cognitive measures were largely unaffected by expectation or stimulation conditions. Overall, our analysis revealed no effect attributable to baseline expectations, belief of group assignment, or experimental condition on behavioral outcomes. Subjective experience did not differ based on expectation or stimulation condition. Conclusions: Our results suggest no clear effects of tDCS or of expectations on our performance measures, highlighting the need for further investigations of such stimulation methods.